GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 564923012 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 564923012 records from 11968 constituent datasets: 588 records from NHT flora. 3786 records from Faun. 14 records from Collection Onychophora - SMF. 338 records from ZFMK DORSA. 274 records from Bernhardsthal. 1027 records from IBF Monitoring of Fungi. 11 records from Zoobenthos in surface sediments off Cape Lucul. 209 records from Relative abundance of coccosphere-units at site GIK23414. 451 records from Nannofossil abundance of Hole 15-148. 3 records from Nannofossil abundance of Hole 31-301. 11505 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 17618 records from BioGIS - Mammals - INPA database. 71 records from (Data S1) Palynology of ODP Site 113-696. 13 records from FND "Weißer Berg" Leißling. 1 records from Waldtag in und um Seelingstädt. 95 records from BIRDRACE BiBi. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 47765 records from National Bat Database of Ireland. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 126 records from Total foraminifera counts from M35/1_MSN1050. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 3 records from Nannofossil abundance of Hole 94-609A. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 66394 records from United States National Plant Germplasm System Collection. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 6 records from Wiese. 16 records from Coccolith counts of multinet M32/5_MSN986. 21 records from Nannofossil abundance of Hole 6-55. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 15389 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 12832 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 2182 records from Ibaraki Nature Museum, Mollusk collection. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 163 records from Planktic foraminifera abundance of Hole 32-313. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 1130 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 36506 records from Plant Specimens of Kurashiki Museum of Natural History. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 3 records from Analyses of the recent components of sediment core PS1215-2. 68 records from Planktic foraminifera abundance of Hole 22-213. 164 records from Planktic foraminifera abundance of Hole 22-215. 26 records from Planktic foraminifera abundance of Hole 20-200A. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 99035 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 875 records from Fish monitoring data in Lake Kasumigaura. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 274 records from Foraminifera abundance of sediment core BM1958.631. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 19 records from Occurrence of mammalia relicts at site Gröbern. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 3 records from Microfossil abundance of Hole 50-415. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 126 records from Planktic foraminifera abundance of Hole 32-305. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 268876 records from Fiji Terrestrial Arthropods. 145 records from Whale log - observations from ANARE voyages. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 17 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 9421 records from The Orchid Atlas of Western Australia. 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 251763 records from Moths Ireland. 117 records from Wassermann. 105 records from BIRDRACE coesfelder_vogelkundler. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 101 records from MVZ Mammal Observations (Arctos). 3204 records from Faunal Inventory of Morysin Nature Reserve. 176654 records from CAS Entomology (ENT). 73 records from VFD-HH/SH: Pferdweide Lammert. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 910 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 83 records from Planktic foraminifera abundance of Hole 14-135. 211497 records from R. L. McGregor Herbarium Vascular Plants Collection. 2 records from Abundance of benthos infauna at station GIK23025-2. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 22 records from Phytoplankton abundance at bottle station GOM6/1. 87 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 61 records from Fürstenberger Ralley Teil 3. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 1114 records from MEXU/Tipos de plantas vasculares. 14635 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1 records from Planktic foraminifera abundance of Hole 8-72. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 257 records from Kernberge und Umgebung (Jena). 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 211338 records from MVZ Mammal Collection (Arctos). 116639 records from The digitization of plant specimens of NTU. 5240 records from Nordic Genetic Resources. 18 records from Meiofauna abundance in sediment core 13368-015. 9402 records from MEXU/Plantas Vasculares. 82634 records from Vascular Plants, Observations, Oslo (O). 29 records from Klimaoasen in Köln. 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 28 records from Occurrence of mammalia relicts at site Climauti II. 1351 records from Neogene palynomorpha from site 93-603, part 1. 2357 records from Foraminifera abundance of Hole 17-167. 525 records from Planktic foraminifera abundance of Hole 94-609. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 1116033 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 308 records from Planktic foraminifera counts of sediment core V19-178. 19017 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 14473 records from Ontario Breeding Bird Atlas 1981-1985. 46 records from An der Ohm, (Wettsaasen). 18038 records from Sponges of Rathlin Island. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 157666 records from Field Museum of Natural History (Zoology) Mammal Collection. 35 records from Gym Freyung. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 2997 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 61 records from Plant specimens of Hokkaido University Museum. 1056 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 70 records from Exotic terrestrial flatworms, Macquarie Island. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 101 records from Birdrace-Herford-Birder-Herford. 16695 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 1528 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 15 records from AKG-Bensheim. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 66 records from Foraminifera abundance of Hole 55-432A. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 748 records from Moluscos Marinhos de Augusto Nobre. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 12645 records from Mycology Herbarium, Trondheim (TRH). 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 175 records from Mycological collections of the University of Tartu. 4935 records from Herp Collection. 388 records from Mooswald (Freiburg). 30 records from Benthic foraminifera abundance of Hole 42-379A. 53 records from Planktic foraminifera abundance of Hole 29-281A. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 72 records from Faunal assemblage of sediment core TR149-35. 2233 records from Chrysomelidae of Poland. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 3 records from Collection Xiphosura SMF. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 2120907 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 6115 records from Chinese mitten crab (Eriocheir sinensis) occurrences in Flanders. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 20 records from Mikroorganismen. 48 records from Wahner Heide LK 12 Biologie. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 1 records from Results of palynological analysis of Hole 302-M0004C. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 1404 records from Arachnologie - SMNG. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 3 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 3191 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 939 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 97 records from LauWi. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 64 records from Feuchtbiotop Weidenkaule. 56 records from Nannofossil abundance of Hole 94-607. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 12 records from Ficha de Sonora aemula. 90 records from Schulhof Bühlschule Giengen. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 114 records from BIRDRACE VIE will rock you!. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 9 records from Nannofossil abundance of Hole 60-455. 21 records from Nannofossil abundance of Hole 24-232A. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 2 records from Kirchenforst. 115 records from Nannofossil abundance of Hole 29-279A. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 61226 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 10506 records from The Erysiphales Collection at the Botanische Staatssammlung München. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 22 records from Nannofossil abundance of Hole 9-83A. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 5 records from Analyses of the recent components of sediment core PS1400-4. 2022 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 1723 records from KTU Pinophyta. 30 records from Nannofossil abundance of Hole 8-71. 1305 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7069905 records from Great Backyard Bird Count. 131 records from Unser Schulhof - eine Apotheke. 48 records from Freiheitsring (Frechen). 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 186 records from Total foraminifera counts of multinet M21/1_MSN604. 70 records from Parkuntersuchung Weißer See. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 271 records from Planktic foraminifera counts of sediment core RC11-147. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 3761 records from Mountain Invasion Research Network (MIREN) survey. 12025 records from Arizona State University Amphibian and Reptile Collection. 22 records from Sediment properties of core PLG95B_06BOXG. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 8 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 5733 records from Small Mammal Research Database. 353 records from Colección de Entomología - Arthropoda. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 400 records from Harpactus Shuckard. 241 records from Planktic foraminifera abundance of Hole 67-499B. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 140142 records from Bernice P. Bishop Museum. 69595 records from Lepidoptera collection, Natural History Museum, University of Oslo. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 84521 records from BioGIS - Vascular plants - INPA database. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 160 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Trockenrasen bei Dörndorf. 47 records from Schulgelände Ceciliengymnasium. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 827 records from ZFMK Sound Archive. 9758 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 2194 records from Algae, Specimens, Agder naturmuseum (KMN). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 35266 records from Kathryn Kalmbach Herbarium. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 6056 records from Lichens of Knyszyn Forest. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 135 records from Total foraminifera counts of multinet M21/3_MSN688. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 19 records from Nannofossil abundance of Hole 31-298. 76 records from Coccoliths in sediment core PS1533-3. 315 records from Planktic foraminifera counts of sediment core RC17-69. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 103 records from BIRDRACE Die Otzberger. 84 records from BIRDRACE Birding for Nature. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 6 records from Nannofossil abundance of Hole 7-63. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 672 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 57 records from Nannofossil abundance in sediment core PS1311-4. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 184156 records from The Flora of County Waterford. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 181 records from Collection Crustacea ZMG. 94 records from Coccolith counts of multinet SO119_MSN1298. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 6 records from Sediment properties of core PLG93_BCORE1. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 4826 records from Vascular Plants Collection of National Museum of Nature and Science. 32698 records from Fish tag database. 36301 records from Pelagic Fish Observations 1968-1999. 13723 records from Impetus - Herbarium Hamburgense. 302 records from Stadtpark Sulzbach-Rosenberg. 168 records from Weidenhüttendorf an der Würm (München). 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 778 records from Planktic foraminifera abundance of Hole 40-362. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 2928 records from Homoptera. 1582375 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 1130 records from Ostracoda in sediment core PS51/154-11. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 40 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 1028826 records from SEAMAP - marine mammals, birds and turtles. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 1 records from Planktic foraminifera abundance of Hole 54-420A. 774 records from Planktic foraminifera abundance of Hole 80-549A. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 7 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 367 records from Collection Crustacea - KAUMM. 310 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 10466 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 588 records from Relative abundance of ostracods in sediment core Lz1120. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 86 records from Fliegenhaupt Marksuhl. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 235 records from Total foraminifera counts from multinet M31/3_MSN905. 10234 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 99 records from Planktic foraminifera abundance of Hole 94-610E. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 107 records from BIRDRACE Herford Birders. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1 records from Hausgarten. 869 records from Lepidoptera Observations from New Zealand by Donald Hobern. 1393 records from Rancho Grande. 3 records from CNIN/Mantodea. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 2 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 12 records from Abundance of radiolaria at station LV28-40-2. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 441 records from Pollen analysis of surface samples from Germany and Austria. 5 records from Memorial University Botanical Garden Collection. 24402 records from Ibaraki Nature Museum, Arthropoda collection. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 2839 records from Rocky Shore Macroalgae. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 145 records from privater Garten. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 177 records from Donauinsel des BN bei Entau. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 320 records from Myxomycetes collection of the University of Eastern Finland. 175 records from INSECT COLLECTION. 93 records from Südwestlich der Parkwiesen. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 2 records from Benthic foraminifera abundance of Hole 42-376. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 1 records from Pollen and spore abundance of Hole 42-379A. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 30889 records from MEXU/Asteraceae. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 107 records from Planktic foraminifera abundance of Hole 18-180. 25 records from Benthic foraminifera abundance of Hole 1-4. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 3481 records from Irish National Frog Database. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 1554 records from Biodiversidad de Datura (Solanaceae) en México. 9715 records from Birds of Ireland. 531415 records from Swiss National Butterflies Databank. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 10883 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 2846 records from Coleoptera, NEF. 256 records from BIRDRACE Upupa epöpse. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 6 records from UWYMV Herpetology Collection (Arctos). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 77 records from Total foraminifera counts from M35/1_MSN1075. 599 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 3 records from Antarctic Arrow worms. 107 records from 1st Austrian Birdrace (Wien). 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 98 records from BIRDRACE Die Paradiesvögel. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 6 records from Nannofossil abundance of Hole 55-430B. 12 records from Abundance of radiolaria at station LV28-44-1. 356 records from Biotope in Rheine - Aktion 350. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 144 records from BIRDRACE Punkbirder Helgoland. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 76 records from Colección de Entomopatógenos de México (CNRCB). 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 679 records from Results of palynological analysis of Hole 302-M0004A. 91 records from Benthic foraminifera abundance of Hole 84-569A. 13639 records from Senckenberg - CeDAMar Resource. 7795 records from Hymenoptera collection, Natural History Museum, University of Oslo. 52 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 402 records from Tag der Artenvielfalt in Heidelberg. 9614 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 49 records from Collection Thysanoptera SMF. 84 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 1378 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 279 records from Planktic foraminifera abundance of Hole 11-98. 44 records from Flora und Fauna in unserer Kita. 53 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 87 records from Klütwald. 57 records from Garten in Schmölln. 18 records from Landschaftsschutzgebiet Buchhorst2. 347 records from (Table 4) Standing stock values of important species in surface sediments. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 6660 records from Weevils of the Tatra Mts.. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 194 records from Collection Cnidaria - ZMB. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 180 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 5 records from Streuobstwiese (Mittelgasse 4). 153 records from Selztal bei Friesenheim. 33 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 21 records from Meiofauna abundance in sediment core 13077-006. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 2088 records from Benthic foraminifera of sediment core MD99-2286. 120611 records from Arizona State University Lichen Collection. 53606 records from BioMar - LIFE project. 214 records from Binsenwiesen. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 4 records from Estimated plankton abundance at station PS63/064-6. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 49637 records from Monitoring data from the federal state Hesse (Germany). 13600 records from Mammal collection, Natural History Museum, University of Oslo. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 45 records from Nannofossil abundance of Hole 28-265. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 85922 records from Mammal specimens. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 57 records from Occurrence of mammalia relicts at site Moladova V. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 231 records from Gunma Museum of Natural History, Fish Specimen. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 38973 records from Herbarium (UNA). 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 8 records from Pollen and spore abundance of Hole 42-380. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 6987 records from National Trust - Ickworth species data held by The National Trust.. 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 9572 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 1128 records from Southern Ocean Ostracoda (except Halocypridina). 1042 records from Planktic foraminifera abundance of Hole 37-333. 764 records from BioGIS - Fish - INPA database. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 764 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 4749167 records from Australia's Virtual Herbarium. 1 records from Planktic foraminifera abundance of Hole 8-73. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 246 records from Benthic foraminifera abundance of Hole 73-524. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 36384 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 117194 records from Mycology herbarium, Oslo (O). 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 114 records from BIRDRACE Di-Bi-Di-Birder. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 717 records from Alterra (NL) - Microarthropods inventory in militairy zone Leusderheide. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 493436 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 4 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 19729 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 8 records from Krittenhorster Wald (Ostkilver). 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 2 records from Nannofossil abundance of Hole 6-49. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 194 records from Colección Herpetológica de la Patagonia. 133180 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 20742 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 3801039 records from FlorKart - FlorenKartierung Gefaesspflanzen. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 96687 records from Invertebrates Collection of the Swedish Museum of Natural History. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 921 records from Planktic foraminifera counts of sediment core RC14-37. 23879 records from svalbardflora.net. 113 records from Collection Hydrozoa - ZMB. 26 records from Schulteich Heinrich-Mann-Schule. 145 records from Phytoplankton abundance at station CD46_0405C#7. 12 records from Lepidoptera specimen database of Japan. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 961 records from Spencer Entomological Museum. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 1 records from Diatom abundance of Hole 95-613. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 129 records from Myriapoda - SMF. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 11 records from Observation of birds at station PS14/156 along 49° West. 1267 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 141 records from Schulhof und Anlagensee in Nellingen. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 6 records from Planktic foraminifera abundance of Hole 23-226. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 304812 records from Observational database of Icelandic plants. 4191 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 72565 records from North Carolina State Museum of Natural Sciences Fishes Collection. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 32 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 78799 records from natagora-earlybirds. 11779 records from MfN - Fossil plants (Cenophytic). 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 86 records from Pollen analysis of sediment core GIK16856-2. 10930 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 296 records from DJH. 2148 records from Eppingen und Umgebung. 269 records from 3. Tag der Artenvielfalt Hockenheim. 76 records from Occurrence of mammalia relicts at site Vindija. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 271 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 27 records from Zwickau- Schwanenteich. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 15851 records from UPCB - Herbário do Departamento de Botânica. 31305 records from MSB Bird Collection (Arctos). 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 814416 records from Fauna Atlas N.T.. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 163 records from Tiere und Pflanzen am Pfannenbach. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 53949 records from Fish Specimens. 140845 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 767 records from BioGIS - Bats - Asaf Tsoar database. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 2913 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 30 records from Leben auf einer Sturmfläche. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 87 records from Total foraminifera counts of trap L2_92_B49. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 5 records from Tuttlinger Tag der Artenvielfalt. 18 records from Meiofauna abundance in sediment core 13200-012. 497 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 12696 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 2991 records from Millenium Seedbank (MSB). 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 4 records from Nannofossil abundance of Hole 29-281A. 14 records from Nannofossil abundance of Hole 85-573. 316 records from Planktic foraminifera counts of sediment core V14-101. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 5318 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 190 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Analyses of the recent components of sediment core PS1215-2. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 11 records from Nannofossil abundance of Hole 6-56B. 32120 records from SBMNH Vertebrate Zoology. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 759 records from Planktic foraminifera abundance of Hole 47-398D. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 144 records from Total foraminifera counts of multinet M21/2_MSN640. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 28 records from Nannofossil abundance of Hole 26-253. 5862 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 35 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 18 records from Planktic foraminifera abundance of Hole 32-310. 692 records from Planktic foraminifera abundance of Hole 40-360. 94 records from Planktic foraminifera abundance of Hole 80-550. 878 records from Planktic foraminifera abundance of Hole 84-568. 99174 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 73 records from Planktic foraminifera abundance of Hole 2-11. 70 records from Planktic foraminifera abundance of Hole 84-569A. 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 4146 records from Marie-Victorin Herbarium (MT) - Bryophytes. 16905 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 86071 records from NINA Vanndata øvrige arter. 13 records from Tag der Artenvielfalt am Bruckenwasen. 161 records from BIRDRACE Nord-Seh-Team. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 26 records from Ostracoda abundance of Hole 13-132. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 71 records from Collection Graptolithina fossil SMF. 1 records from Abundance of benthos infauna at station GIK23004-3. 57214 records from Insect Collection of Taiwan Forestry Research Institute. 7 records from Additions to the myxobiota of the Åland Islands. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 1 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 4004 records from Sightings Map of Invasive Plants in Portugal. 99 records from Düne am Ulvenberg (Darmstadt). 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 23215 records from rmca-albertine-rift-butterflies. 20 records from Motzener Tonsee. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 12 records from Nannofossil abundance of Hole 20-200. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 24 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 48913 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 3 records from Fledermauserlebnistag für Kinder am Laacher See. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 244 records from WildesMoor bei Schwabstedt. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 92 records from Siliceous microfossil occurrence, Site 177-1094. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 16 records from Dinoflagellate cysts of surface sediments. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 21074 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 52865 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 43557 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 3 records from Nannofossil abundance of Hole 51-417D. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 76590 records from University of British Columbia Herbarium (UBC) - Algae Collection. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 9 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 59 records from Biological Records Centre - RISC Non-Native Species Records for Muntjac. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 52 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 281250 records from Quadrige. 168034 records from Essig Museum of Entomology. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 45 records from Parcela Permanente en el Pantano Martos. 264743 records from ArtenFinder. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 237 records from RSPB - Capercaillie national surveys (SCARABBS). 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 772 records from Fishes of the Congo River 2010 Expedition. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 310 records from Lepidoptera collection, NTNU, Trondheim. 9948 records from Bees of Canada / Gschwendtner property collection. 54 records from Wiese am Unterbecken. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 6 records from Ökosysteme rund um Wedel. 1421 records from Cowan Tetrapod Collection - Herpetology. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 8 records from Abundance of radiolaria at station LV28-29-1. 2 records from Smear slide analysis of sediment core GeoB7427-2. 16 records from Nannofossil abundance of Hole 47-398B. 66 records from Range table from ostracoda in ODP Hole 151-910D. 25554 records from Formidabel; Belgian Ants Database. 642 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 1627 records from The Irish Squirrel Survey 2007. 404 records from Greater Manchester Ecology Unit - Water Vole Distribution for Greater Manchester. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 7015 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 29470 records from Phanerogamic Botanical Collections (S). 146855 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 364183 records from University of Florida Vertebrate Paleontology. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 84 records from BIRDRACE Vogelscheuchen. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 19512 records from MfN - Fossil invertebrates Ia. 104 records from Ross Sea Pycnogonids. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 2 records from Nannofossil abundance of Hole 74-526. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 21447 records from Herbarium de Geo. B. Hinton, México. 131 records from Artenvielfalt auf dem Schulgelände. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 4 records from Collection Pantopoda SMF. 15764 records from Naturalis Biodiversity Center (NL) - Porifera. 8399 records from NYSM Birds. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 102 records from Ostracod abundance in sediment core Lz1120. 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 535 records from Benthic foraminifera abundance of Hole 73-522. 460 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 27 records from Benthic foraminifera abundance of Hole 34-320A. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 14 records from Nannofossil abundance of Hole 8-72A. 14997 records from iziko South African Museum - Fish Collection (AfrOBIS). 555 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 23055 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 8979 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 155 records from Bergbaufolgelandschaft am Muldestausee. 741 records from Planktic foraminifera abundance of Hole 20-200. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 8 records from Occurrence of mammalia relicts at site Wretton. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 84731 records from Herbarium of Umeå University (UME). 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1983 records from Seabird 2000. 3042 records from dec2011. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 7685 records from European riparian ground beetles. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 57 records from Schulgarten Janusz-Korczak-Realschule. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 349105 records from BSBI tetrad data for Ireland. 9088 records from Flora of Słowiński National Park, Poland. 2633 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 48 records from Diatom assamblage in samples from sediment trap OG5. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 777 records from Planktic foraminifera counts of sediment core RC17-108. 69 records from BIRDRACE Mathilden-Käuze. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1443 records from Odonata of the Congo River 2010 expedition. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 112 records from BIRDRACE Gütersloher Gimpel. 11370 records from Distribution of planktic foraminifers of core V22-174. 44 records from Planktic foraminifera abundance of Hole 19-188. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 241 records from BIRDRACE RennVögel Münsterland. 67 records from Tongrube bei Hettstedt. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 4094 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 15 records from Herdengelhoehle taxa and datings. 102 records from Benthic foraminifera abundance of Hole 42-372. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 70467 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 45 records from Wasser-Lernort Nettemündung. 70615 records from Marsh Monitoring Program - Birds. 520 records from Planktic foraminifera abundance of Hole 39-357. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 4339 records from CHAS Mammalogy. 100 records from Birdrace-The_Ringers-Friesland. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 1 records from Antarctic Marine Amoebae. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 2083 records from Planktic foraminifera abundance of Hole 72-517. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 1511 records from The French Collection of Medicago truncatula. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 10577 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 1 records from Boraginaceae (Cynoglossum cherangauiense). 3 records from Fundación Miguel Lillo - Colección Ornitológica. 24 records from Occurrence of mammalia relicts at site Overmere. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 1 records from Microfossil abundance of Hole 42-378. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 1 records from Abundance of benthos infauna at station GIK23062-2. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 19 records from Dinoflagellate abundance of Hole 81-553A. 428 records from EAN - Herbário Jaime Coelho de Moraes. 147 records from NABU-Auerochsenweide. 212 records from Nanoplankton abundance at station GeoB2017-1. 180 records from Range table from ostracoda in ODP Hole 144-871A. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 96 records from Birdrace-federleser-Herford. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 1121 records from ZFMK DORSA. 349 records from Planktic foraminifera counts of sediment core V20-170. 5732 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 845 records from Estudio comparativo del zooplancton en dos regiones de México. 4542 records from Ibaraki Nature Museum, Algae collection. 20 records from Crispin S. Guppy Observational Records. 10326 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 57 records from Heidesee / Halle. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 42 records from Foraminifera abundance of Hole 24-236. 498 records from Dinoflagellate abundance of Hole 94-611C. 12672 records from MVZ Egg and Nest Collection (Arctos). 16 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 36 records from Nannofossil abundance of Hole 14-141. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 19680 records from BC Coastal Waterbird Survey. 35345 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 8547 records from Individual Sightings. 38330 records from Botanical Museum, Copenhagen, Mycology Herbarium. 2141754 records from Biologiezentrum Linz. 5860 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 379 records from UAM Herpetology Collection (Arctos). 5086 records from Spider Mites Collection of Jean Gutierrez. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 11034 records from The Bat Conservation Trust - Noctule, Serotine and Pipistrelle Field Survey. 139 records from Siliceous microfossil occurrence, Site 177-1093. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 1997 records from Aves de la cuenca media del río Bogotá. 71586 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 172 records from Foraminifera abundance of Hole 59-448A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 39423 records from Irish vascular plant data 1999-2009. 14153 records from Entomology at ZMUC, Natural History Musem of Denmark. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 1077 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 9 records from Nannofossil abundance of Hole 1-2. 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 8 records from Nannofossil abundance of Hole 49-412A. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 294 records from Naturgarten Langenholtensen. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 8293 records from Collection Bryozoa SMF. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 1 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 148 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 91 records from BIRDRACE SchrägeVögel. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 140022 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 236 records from GENT Lactarius Deliciosi. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 169 records from Planktic foraminifera counts at CTD station PS55/051. 76 records from Faunal assemblage of sediment core GS7603-10. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 753 records from Planktic foraminifera counts of sediment core V28-127. 1101 records from Relative abundance of ostracods in sediment core Co1202. 143 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 35 records from Nannofossil abundance of Hole 78-543. 7 records from Nannofossil abundance of Hole 38-336. 596 records from Planktic foraminifera counts of sediment core A15-558. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 6 records from Nannofossil abundance of Hole 6-49. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 591 records from Planktic foraminifera counts of sediment core V16-25. 2027 records from Bryophyte collection of Jyväskylä University Museum. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 1023 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 200 records from EASIANET. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 1298 records from Planktic foraminifera abundance of Hole 23-219. 371 records from Planktic foraminifera abundance of Hole 63-470. 21 records from Vogelwelt im Europa-Rosarium. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 65 records from BIRDRACE Federal Birds of Investigation FBI. 248 records from Schulgarten der Volksschule. 33 records from Schüler erforschen die Helme-Aue. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 11964 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 7501 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 82736 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 19 records from Microplankton data off Mejillones, 2006, Chile. 84 records from Benthic foraminifera abundance of Hole 84-566C. 38 records from Microfossil abundance of Hole 21-206C. 1 records from Dinoflagellate abundance of Hole 19-183. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 74219 records from Royal Botanic Garden Edinburgh Herbarium (E). 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 8100 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 75981 records from Irish Vascular Plant Data - Paul Green. 18643 records from Endemic plants of the Congo basin. 65435 records from CAS Ornithology (ORN). 95 records from Vielfalt verschiedener Wiesen. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 85422 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 150474 records from KU Museum of Invertebrate Paleontology. 8169 records from CRI - Herbário Pe. Dr. Raulino Reitz. 173580 records from Mammalogy Collection - Royal Ontario Museum. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 39 records from Red list project inventory, fungi. 17 records from Hazel Dormouse in Ireland. 85 records from Birdrace-Die_Paradiesvögel-Herford. 3 records from Blankenfelder See. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 16076 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 44590 records from Tasmanian Museum and Art Gallery provider for OZCAM. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 8523 records from Distribution of planktic foraminifers of core RC24-16. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 7 records from Analyses of the recent components of sediment core PS1219-1. 1406 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 43 records from Schulgelände Thurmair-Gymnasium. 504 records from Schatzinsel Wangerooge. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 16 records from Nannofossil abundance of Hole 9-77B. 129 records from Nannofossil abundance of Hole 29-284. 8 records from Nannofossil abundance of Hole 49-409. 260 records from Range table from ostracoda in ODP Hole 144-873B. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 14941 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 68077 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 495 records from Life Science National Tsing Hua University. 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 239 records from Naturerlebnisraum Koppelsberg. 186 records from Planktic foraminifera abundance of Hole 94-610. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 15 records from Occurrence of mammalia relicts at site Dendermonde. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 21 records from Collection Ctenophora SMF. 6 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 4728 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 19728 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 83531 records from UCJEPS TAPIR Provider. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 50 records from Planktic foraminifera abundance of Hole 60-457. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 1346 records from Weevils of Poland. 4719 records from IBF Monitoring of Lichens. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 59180 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 260 records from Speothos Venaticus por Guillermo Gil. 3 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 233 records from Föhrenried (Fronreute und Baindt). 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 783 records from Phytoplankton abundance in surface water during cruise CD61. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 745758 records from Museum of Comparative Zoology, Harvard University. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 5 records from Schulwald Regionale Schule Sprendlingen. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 7 records from Nannofossil abundance of Hole 5-33. 7 records from Nannofossil abundance of Hole 9-82A. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 15 records from Microfossil abundance of Hole 59-450. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 9 records from Coccolith counts of multinet M32/5_MSN982. 5 records from Nannofossil abundance of Hole 84-569. 3 records from Nannofossil abundance of Hole 22-212. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 351 records from Great Lakes Forestry Centre Insect Collection. 14693 records from The Gordon Alexander Orthoptera Collection. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 4 records from Nannofossil abundance of Hole 52-418. 5943 records from UWBM Herpetology Collection (Arctos). 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 593 records from Ostracoda in sediment core PS51/159-10. 576 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 1249 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 157033 records from The Himalayan Uplands Plant database (HUP Version 1). 40550 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 354 records from Foraminifera distribution of sediment core KS310. 41 records from Altholzparzelle Eilenriede Hannover. 125 records from Artenbestimmung. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 56 records from Estetal (Buxtehude). 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 249 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 353 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 896 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 2069 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1254 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 14563 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 4707 records from Lyman Entomological Museum. 3 records from Planktic foraminifera abundance of Hole 54-424B. 325 records from Planktic foraminifera abundance of Hole 32-305. 164 records from Planktic foraminifera abundance of Hole 94-610B. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 94 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 3406 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 308 records from Wangerooge. 149 records from Bayerische Donau - Neu Ulm. 703 records from Planktic foraminifera counts of sediment core V25-59. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 32468 records from MedOBIS (EurOBIS). 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 176144 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 439 records from Antarctic and Subantarctic Asteroid zoogeography (SCAR-MarBIN: Antarctic OBIS). 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 76 records from The Ants of Bulgaria. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 15 records from Kühnauer Aue und Kühnauer See. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 233 records from Total foraminifera counts from M35/1_MSN1044. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 3 records from Nannofossil abundance of Hole 9-80. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 238 records from Coccoliths in ODP Hole 104-643A. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 45 records from Antarctic Isopods. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 353 records from Stadtgebiet (Dannenberg). 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 80 records from BB-Biodiversität b. 5238 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 2 records from Nannofossil abundance of Hole 29-280A. 32 records from Nannofossil abundance of Hole 67-499. 316 records from Planktic foraminifera counts of sediment core RC11-86. 317 records from Planktic foraminifera counts of sediment core RC14-29. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 35 records from Ortsrand Zandershagen. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 12 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 4256 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 5 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 16 records from Abundance of radiolaria at station LV28-3-3. 60 records from Planktic foraminifera abundance of Hole 19-192. 161946 records from UA Herbarium. 2182 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 28 records from Stadtpark Prinzengarten (Sigmaringen). 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 6 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 892 records from Weevils of Wales and England. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 3633 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 180 records from Paul-Gerhardt-Schule Dassel. 89 records from Birdrace-Team_Wangerooge-Friesland. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 269 records from BIRDRACE Dithmarscher Deichhühner. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 19122 records from Biological Records Centre - Cerambycidae Dataset. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 100 records from Grenzturm Hohen Neuendorf. 40 records from Tiere und Pflanzen um uns herum !. 135 records from Waldi-Weiher. 5 records from Fledermäuse u. nachtaktive Insekten. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 185 records from Abundance of coccosphere-units of site GIK23414. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1015 records from Irish Marine Turtle Database. 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 1472 records from Herbarium Rhoenmuseum Fladungen. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 85 records from Sedimentological investigation on core V25-45. 2 records from Nannofossil abundance of Hole 7-64A. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 482 records from Kühmark bei Wetzlar. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 50 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 10 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 203 records from Planktic foraminifera abundance of Hole 72-515B. 48 records from Benthic foraminifera abundance of Hole 42-380A. 691 records from RSPB - Black grouse national surveys (SCARABBS). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 122 records from Phytoplankton abundance at station CD46_1005C#4. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 31 records from Nannofossil abundance of Hole 4-23. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 23 records from Landwehrbach. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 1377 records from Red list project inventory, lichens. 525 records from Benthic foraminifera abundance of Hole 40-360. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 35798 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 76 records from BIRDRACE Nachtigallen. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 58 records from Lüner Holz (Lüneburg). 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 3508 records from Entocytheridae (Ostracoda) World Database. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 10744 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 2570 records from Invertebrates compiled by W.Block. 92 records from Nottekanal, Klasse 7 - 10. 1202 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 1636 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 5993 records from HRCB - Herbário Rioclarense. 567 records from Collection of Hymenoptera. 198 records from Total foraminifera counts from M35/1_MSN1047. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 60 records from Schafsweide Seniorenhaus Berghof. 61 records from BIRDRACE Baumläufer. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 501 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2321 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 5 records from Analyses of the recent components of sediment core PS1216-1. 4903 records from UCM Bird Collection (Arctos). 786 records from Planktic foraminifera abundance of Hole 72-518. 8 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 7470 records from National Taiwan University. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 90 records from Planktic foraminifera counts of sediment core RC13-158. 704 records from Planktic foraminifera counts of sediment core V18-207. 63 records from Planktic foraminifera counts of sediment core V19-21. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 20 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 7034 records from Mollusca collection of National Museum of Nature and Science. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 181 records from Alien Species in Poland - Animals. 12 records from Art´n Vielfalt im Kinderwald. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 4 records from Nannofossil abundance of Hole 16-156. 92 records from Nannofossil abundance of Hole 31-296. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 20 records from Nannofossil abundance of Hole 7-63A. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 9904 records from CUMV Mammal Collection (Arctos). 7551382 records from BirdLife Australia, Birdata. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 102 records from Birdrace-OAG_Neuwerk-Hamburg. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 1294 records from MfN - Fossil vertebrates III. 4 records from Range table from nannofossils in ODP Hole 139-857A. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 483 records from Artenvielfalt im Rhein-Neckar-Raum. 69 records from Mönchspark. 31 records from Bayerische Donau - Tapfheim. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 429 records from Larval fish at Helgoland Roads in 2004. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 7811 records from Institut Botanic de Barcelona, BC-Histórico. 7 records from Nannofossil abundance of Hole 27-259. 14 records from Nannofossil abundance of Hole 14-140. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 2 records from Chaetognatha - SMF. 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 106 records from Arteninventar rund um den Rannahof. 1197 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 307 records from Schlichemquelle (Tieringen/Meßstetten). 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 27 records from Pollen data of trap CB3. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 56 records from Zitadelle Berlin-Spandau (7b). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 54 records from Biotope im Schulumfeld. 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 137 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 191 records from Foraminifera abundance of sediment core C1960.202. 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 29992 records from Natural History Museum, University of Tartu. 3 records from Dinoflagellate abundance of Hole 85-572. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 1159 records from Countryside Council for Wales - Bat Roosts Database - North East Wales. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 465 records from Philosophenwald und Wieseckaue in Gießen. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 1641 records from Arácnidos de Centroamérica. 181 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during MSM13/3 and MSM 13/4 cruises (2009). 23 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 111581 records from Highland Biological Recording Group - HBRG Insects Dataset. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 57 records from Schulgarten Fichteschule. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 15 records from Urwald 2 (Bad Waldsee). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 3466 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 10 records from Oberservation of birds at station PS14/143 along 49° West. 87143 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 873 records from Kartlegging av spredning av fremmede bartrær. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 4 records from Nannofossil abundance of Hole 55-430A. 137 records from Planktic foraminifera counts of sediment core V28-25. 89 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 3382 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 1059 records from Planktic foraminifera abundance of Hole 15-148. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 59 records from Schulteich Freie Waldorfschule Darmstadt. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 107 records from Bases de datos de Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 23 records from AlgaTerraMovies. 376 records from Wupperaue bei Kemna (Wuppertal). 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 41 records from Örtzemündung (Stedden). 232 records from Distribution of planktic foraminifera of sediment trap OG5. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 7924 records from Dinoflagellate cysts in surface sediments. 12 records from Nannofossil abundance of Hole 74-528A. 2 records from Nannofossil abundance of Hole 18-174A. 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 19 records from Pollen record from Mamontovy Klyk. 479 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P5. 159 records from Total foraminifera counts of multinet SO118_MSN1251. 39 records from Calcareous dinocysts along profile Ruegen. 22 records from Phytoplankton abundance at bottle station GOM1/6. 18750 records from National Trust - Hatfield Forest species data held by The National Trust.. 171 records from Sahrbachtal Kreis Ahrweiler. 18 records from Smear slide analysis on sediment core GeoB4206-1. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 79 records from Umgebung von Schorndorf. 327 records from Foraminifera abundance of Hole 58-443. 751 records from Planktic foraminifera abundance of Hole 49-408. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 264 records from Planktic foraminifera counts of sediment core RC12-339. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 3093 records from Biological Records Centre - Mosquito Recording Scheme. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 50476 records from Flora d'Andorra. 23 records from Benthic foraminifera abundance of Hole 93-603. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 15 records from MVZ Herp Observations (Arctos). 15817 records from UFP - Herbário UFP - Geraldo Mariz. 3489 records from Polish seed gene bank – historical passport data of accessions. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 13 records from Foraminifera abundance of Hole 57-438B. 49 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 28 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 2694 records from Recuento de la diversidad florística de Veracruz. 16277 records from Birds Specimens. 321 records from Fuldaaue (Stadtgebiet Fulda). 1571 records from Diptera, NEF. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 5962 records from Broadland Environmental Services Limited - Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 1658 records from MISE Project Waterford Otter Records, 2011-2015. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 185 records from (Table 2) Abundances of dinoflagellates in ODP Hole 105-646B. 1972 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 661 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 475 records from Herp specimens. 778 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species: Great crested newts. 173 records from (Table T3) Stable isotope ratios and abundances of foraminifera from ODP Hole 172-1063D. 65079 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 521 records from Bayerische Donau - Leipheim. 2 records from Nannofossil abundance of Hole 10-87. 17 records from Coccoliths in sediment core PS1527-2. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 8063 records from Vascular Plants Collection of Sagamihara City Museum. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 84 records from BIRDRACE Avinauten. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 2733 records from Anfibios y reptiles del estado de Querétaro. 989 records from BÜG. 4 records from Zwischen Enz und Schule. 7341 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 1 records from Occurrence of mammalia relicts at site Egtved. 59 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 6113 records from Hongos del estado de Veracruz. 236 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 3763 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 133 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 765 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 9420 records from Sussex Biodiversity Record Centre - Sussex Bryophyte Atlas Data edited by Howard Matcham. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 73 records from Tiergarten (Zeitz). 1017 records from Planktic foraminifera abundance of Hole 26-253. 3 records from Planktic foraminifera abundance of Hole 54-419. 876 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 103 records from Birdrace-Die_Nachtigallen-Herford. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 41915 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 500 records from Foraminifera abundance of Hole 48-404. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 284708 records from Balfour-Browne Club - Water Beetle Surveys from Britain and Ireland. 107 records from Hypogean Crustacea of Ireland. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 347 records from Planktic foraminifera abundance of Hole 21-209. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 80 records from Total foraminifera counts of multinet M12/3_MSN543. 2 records from Nannofossil abundance of Hole 66-488. 354 records from Microfossil abundance of Hole 35-323. 72 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 88 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 1120 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 3669 records from ARKO strandeng. 2183 records from JOI - Herbário Joinvillea. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 3330 records from Herbier A. Le Grand (BOUM). 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 137 records from Corvids Literature Database. 54856 records from Colección de Referencia de Lepidópteros Diurnos Mexicanos de la CNIN (Lepidoptera: Papilionoidea) (IBUNAM). 81 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 35 records from Range table from planktonic foraminifers in ODP Hole 144-873A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 6 records from Fließgewässeruntersuchung am Haselbach. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 11 records from Microzooplankton abundance and biomass at station TT050_21-13. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 1742 records from Eggs Specimen. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_240-4. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 121 records from Relative abundance of radiolaria in surface sediments. 2 records from Nannofossil abundance of Hole 74-525A. 142 records from Ostracoda in sediment core PS51/135-4. 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 94 records from Total foraminifera counts of multinet M21/4_MSN697. 115 records from Total foraminifera counts of multinet PO247/2_MSN1382. 88 records from Total foraminifera counts of trap L2_92_A43. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 72 records from Occurrence of nannoplankton observed in Early Pliocene samples from Zanclean stratotype of Capo Rossello, Sicily (Table I). 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 130 records from Planktic foraminifera counts of sediment core RC11-120. 214 records from Planktic foraminifera counts of sediment core V27-86. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 279 records from Koleopterologen am Bausenberg. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_8-CTD102. 325 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 13 records from CNAN/Pseudoscorpiones. 2910 records from The Erysiphales Collection at the University Halle-Wittenberg. 628 records from Relative abundance of planktic foraminifera in sediment core TR126-29 from the 120 kyr time slice reconstruction. 2 records from Occurrence of mammalia relicts at site Condover. 14 records from Range table from benthic foraminifers in ODP Hole 178-1101A. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 194 records from Bodenteicher Seewiesen. 50 records from Flora und Fauna im Brexbachtal. 247 records from Planktic foraminifera abundance of Hole 63-471. 1848 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 3939 records from Census of plant species in Pahou forest reserve. 204 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1710-3. 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. UADY_SNIB. 654 records from Benthic foraminifera abundance of Hole 56-435. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 6723 records from NOAA HML Tidal Creek Database. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 221 records from Foraminifera abundance of sediment core IN68-5. 1137 records from Planktic foraminifera abundance of Hole 72-516F. 20354 records from R. L. McGregor Herbarium Lichen Collection. 400 records from Distribution of planktonic foraminifera in Oligocene-Miocene of three drill sites from the netherlands Peel area. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 51 records from Taxonomic revision of the spider family Penestomidae (Araneae, Entelegynae). 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 1008 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 8171 records from NCSM Mammals Collection. 4007 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 11 records from Oberservation of birds at station PS14/145 along 49° West. 8493 records from National Invasive Species Database. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 563 records from NRM-Herpetology. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 2 records from Microzooplankton abundance and biomass at station TT050_15-3. 16 records from Nannofossil abundance of Hole 24-235. 23 records from 2. Aspacher GEO-Tag der Artenvielfalt. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 9660 records from Universität Salzburg. 40 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 212 records from Colección nacional de palmas de Colombia - JBQ. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 9866 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 518899 records from Danish Mycological Society, fungal records database. 1131 records from (Appendix A1) Abundances of planktonic and benthic foraminifera in the Turonian to Coniacian sediments of ODP Site 207-1259. 262 records from Planktic foraminifera abundance of Hole 1-3. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 79097 records from All Ireland Non-Marine Molluscan Database. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 3695 records from Distribution of planktic foraminifera in ODP Site 202-1240 samples. 175 records from NPWS Pine Marten database. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 157 records from Total foraminifera counts of multinet M21/6_MSN787. 1984 records from Planktic foraminiferal species counts in GeoB1117-2. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 650 records from Relative abundance of planktic foraminifera in sediment core K708-001. 333 records from Langes Tannen (Uetersen). 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 1763 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 338 records from ConDidact Citizen Science Surveys - Snails 2012. 3477 records from Aves laguna El Tinije. 16 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 230 records from Range table from benthic foraminifera in ODP Hole 199-1220B. 114 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 589 records from (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea. 4965 records from SANT herbarium vascular plants collection. 2011 records from Local BioBlitz Challenge 2013. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 5 records from Dinoflagellates, pollen and spore abundance of Hole 29-280A. 7 records from Oligosarcus perdido (Characiformes, Characidae), a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil.. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 23 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 810 records from Chrysomelidae of the Carpathians. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 139 records from Total foraminifera counts of multinet M42/3_MSN1364. 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 2 records from Nannofossil abundance of Hole 20-199. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 19 records from Meiofauna abundance in sediment core 13200-001. 33 records from Taxonomic revision of the Neotropical Myrmicinae ant genus Blepharidatta Wheeler. 5155 records from Anfibios y reptiles del estado de Nuevo León. 7 records from Analyses of the recent components of sediment core PS1219-1. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 1158 records from Bulk components and planktonic foraminifera of sediment core GeoB7139-2. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 186100 records from Geneva Herbarium – General Collection (G). 3 records from Nannofossil abundance of Hole 39-359A. 12 records from Microplankton abundance at bottle station SEPT-1999-K7. 2 records from Radiolaria assemblage in sediment core GIK23400-3. 9877 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 315 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 41 records from CIM Specimens. 1 records from FTEA. 5 records from Nannofossil abundance of Hole 34-320A. 89 records from Collection Bryozoa - ZMB. 6 records from Sediment properties of core CD86_09_PC. 362 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 266 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3257 records from fundiv france database. 65 records from LSG "Großes Bruch". 95 records from BIRDRACE accipiter hardcore birding. 86 records from (Table 9) Planktonic foraminifer abundance of ODP Site 162-985. 4021 records from (Figure 7) Distribution of benthic foraminifers in the Oligocene to upper Miocene DSDP of Hole 71-513A. 573 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 5834 records from National Lesser Horseshoe Bat Database. 17782 records from The Bat Conservation Trust - Colony Count Survey. 11 records from Pollen profile from sediment core AV14_K2-4. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 5311 records from Natural History Museum Maastricht (NL) - Herbarium. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 14 records from Plasm bearing foraminifera counts from multinet M31/2_MSN893. 155 records from Total foraminifera counts of multinet M10/2_MSN231. 56 records from Total foraminifera counts of multinet M21/5_MSN741. 486 records from Dinoflagellates of sediment core GeoB1523-1. 75 records from Abundance of microzooplankton measured on water bottle samples during POLARSTERN cruise ANT-X/6. 46 records from Phytoplankton abundance at bottle station A9/5. 160 records from (Table 1b) Relative percent abundance of planktic foraminiferal species at DSDP Site 77-536, Late Cretaceous. 47 records from Nannofossil abundance of Hole 64-479. 2 records from Nannofossil abundance of Hole 1-5. 2 records from Nannofossil abundance of Hole 3-20C. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 3 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 265 records from Luderbusch. 14 records from Nannofossil abundance of Hole 94-611A. 254 records from Grünes Germersheim. 153 records from (Table 2b) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Benguela upwelling. 4317 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 34351 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 39650 records from (Table T1) Miocene planktonic foraminiferal stratigraphy of ODP Hole 184-1148A. 22 records from Bayerische Donau - Riedlingen. 132 records from Sukzession Industriebrache. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 38 records from Pollen profile ADR353. 41 records from (Table 3a) Distribution of planktonic foraminiferal tests in sediments from Core NKA-37T. 125271 records from Atlantic Reference Centre (OBIS Canada). 19384 records from Herbario de la Universidad de Arizona, EUA. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 18 records from Occurrence of mammalia relicts at site Steinheim an der Murr. 4 records from Occurrence of mammalia relicts at site Ceremosnica. 326 records from Neogene palynomorpha from site 81-555. 54 records from Planktic foraminifera abundance of Hole 4-23. 5 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 2794 records from Diversidad bentónica de la laguna Celestún, Yucatán. 7 records from Analyses of the recent components of sediment core PS1402-2. 11 records from (Table 5) Distribution of Nuttallides umbonifer and zonal age assignments of Eocene to Oligocene sediments of DSDP Hole 48-400A in the Bay of Biscay. 2059 records from (Table 22) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-594. 3372 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 3 records from Occurrence of mammalia relicts at site Igstadt I. 278 records from Planktic foraminifera abundance of Hole 39-354. 8 records from Planktic foraminifera abundance of Hole 29-278A. 220 records from Foraminifera abundance of Hole 57-440. 253 records from Planktic foraminifera abundance of Hole 24-233. 285 records from (Table 4) Planktic foraminiferal abundance in Oligocene to Early Miocene sediments of ODP Hole 177-1090E on the Agulhas Ridge, South Atlantic. 194 records from Distribution of foraminifera of sediment core GK_32_C. 9614 records from University of British Columbia Botanical Garden Collections (UBCBG). 4 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 3756 records from TEPB - Herbário Graziela Barroso. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 181 records from Spießwoogtal / Königsbruch (Fischbach). 107 records from Müritz-Nationalpark. 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 30 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 79 records from (Table 2) Quarternary ostracod abundance in sediment core CRP-1. 6348 records from (Table 1) Distribution of benthic foraminifera in ODP Site 120-747. 205 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 1145244 records from Australian Museum provider for OZCAM. 1390 records from (Appendix 1) Calcareous nannofossils in ODP Hole 119-738B. 25002 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 495776 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 69 records from Lassentiner Moor (Niepars). 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 9105 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 10 records from Phytoplankton abundance at station Rigel_3_2005-03 in March 2005, Chipana, Chile. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 94 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 4 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3. 24822 records from CAS Mammalogy (MAM). 16 records from Nannofossil abundance of Hole 8-72A. 117 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 113-690C. 1749 records from Distribution of planktic foraminifera of sediment core GIK18287-3. 1787 records from Planktic foraminifera abundance of Hole 80-548. 357 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 264 records from Range table from benthic foraminifers in ODP Hole 146-892A. 61 records from Total foraminifera counts of multinet M21/4_MSN698. 18 records from Nannofossil abundance of Hole 64-481. 1605 records from MEXU/Flora de Oaxaca. 240 records from UAM Mammal Observations (Arctos). 426 records from (Table 3) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-750. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 111 records from Total foraminifera counts of multinet M10/2_MSN219. 26 records from A new trapdoor spider species from the southern Coast Ranges of California (Mygalomorphae, Antrodiaetidae, Aliatypus coylei, sp. nov,), including consideration of mitochondrial phylogeographic structuring. 36 records from Pollen profile from Niantic. 2966 records from Colección de Crustáceos Decápodos Marinos de las Costas Mexicanas (UANL). 208 records from Range table from benthic foraminifers in ODP Hole 144-875C. 7 records from Pollen and spore abundance of Hole 42-380A. 2464 records from Countryside Council for Wales - Bat Roosts Database - North West Wales. 554 records from Portuguese Seaweeds. 876519 records from Naturalis Biodiversity Center (NL) - Botany. 25983 records from Monitoring data from the federal state Bavaria (Germany). 13324 records from Collection of various insect orders, Natural History Museum, University of Oslo. 97 records from Landschaftspark St.Leonhard-Deisendorf. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 4 records from Nannofossil abundance of Hole 29-284A. 167 records from (Table 1) Distribution of nannofossils in DSDP Hole 87-582B. 69 records from Planktic foraminifera counts of sediment core RC17-113. 846 records from Collection Polychaeta - ZSRO. 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 3 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1096C. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 128 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 172-1055B. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 4282 records from Universitat de Girona: HGI-Cormophyta. 170 records from Schlattstaller Tal (Lenningen). 183 records from Distribution of living benthic foraminifera in sediment cores of cruise M77 Leg 1 and 2, 63-2000 µm fraction. 3 records from UFACPZ - Herbário da Universidade Federal do Acre. 90 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1378. 68 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 10 records from Nannofossil abundance of Hole 4-25. 4 records from Wuhle - Brücke/ Mosbacher Straße. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 8909 records from The Lichen Collection at the Botanische Staatssammlung München. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 8927366 records from Botanical Society of the British Isles - Vascular Plants Database. 755 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 717 records from Relative abundance of planktic foraminifera in sediment core TR126-23 from the 120 kyr time slice reconstruction. 53 records from Gyeryonsan Natural History Museum Bird . 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 446 records from Bayerische Donau - Blindheim Donaubrücke. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 9 records from Component analysis of TV-guided grab sampler GeoB10071-5. 56 records from Distribution of species of planktic foraminifera in bottom sediments from Core AK32-3333. 360 records from Revisión taxonómica del género Furcraea (Agavaceae) en México y Guatemala. 2672 records from Estudio biosistemático del género Bouteloua (Poaceae) en México. 33 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 1592 records from (Table 8) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-584. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 1026815 records from Belgian IFBL Flora Checklists (1939-1971). 76 records from (Table T1) Distribution of selected calcareous nannofossils at the Paleocene/Eocene boundary, ODP Hole 208-1266C. 13 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 14337 records from Atlas der Raubfliegen Deutschlands - database. 3800 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 15 records from Regenwasserabfangsbecken (Erlenbach). 279 records from BIRDRACE Wannacks Topti(c)ker. 47 records from Schulgelände Grolland. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1054. 79 records from Sedimentological investigation on core V25-60. 239 records from Size of planktic foraminifera at CTD station M39/4_357CTD-15. 1156 records from Colección Entomológica de la Universidad Tecnológica del Chocó. 11 records from Microzooplankton abundance and biomass at station TT045_15-2. 3219 records from (Appendix Table 2) Absolute abundances of benthic foraminifers in DSDP Site 94-610. 790 records from Range table from ostracoda in ODP Hole 143-865B. 356 records from (Table T2) Calcareous nannofossil stratigraphy in ODP Hole 186-1151C sediments. 782 records from Biodiversidad de Veracruz: Oligochaeta. Annelida. 1539 records from Zoological collections of the University of Tartu. 1239 records from (Table 1) Neogene benthic foraminifers of ODP Hole 120-747A. 273 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 73 records from Faunal assemblage of sediment core GS7603-13. 85 records from Total foraminifera counts from M35/1_MSN1065. 57 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1195. 2 records from Nannofossil abundance of Hole 1-5A. 11 records from Nannofossil abundance of Hole 3-15. 591 records from Planktic foraminifera counts of sediment core V23-100. 67 records from (Table 2) Distribution of ostracodes in ODP Hole 107-650A. 5381 records from Whale catches in the Southern Ocean. 245 records from Fig. 11: Benthic foraminifera assemblage of sediment core MD97-2128. 9 records from Analyses of the recent components of sediment core PS1217-1. 155 records from Birdrace-Gätkes_Erben-Lüneburg. 73 records from Occurrence of mammalia relicts at site Bärenfelsgrotte. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 3 records from Sarcodine counts and carbon biomass at station TT007_9-CTD108. 1098 records from Percentages of planktonic foraminifera species in sediment core V25-60. 174 records from Kühnauer See (Dessau). 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 56 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 33379 records from JPB - Herbário Lauro Pires Xavier. 2415182 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 708 records from Kyoto University Reptile Collection. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 138 records from Phytoplankton abundance at station DI182_11863#1. 48 records from Nanoplankton abundance at station GeoB2005-5. 2774 records from Relative abundance of planktic foraminifera in sediment core GeoB1523-1. 63701 records from Chinese Institute of Biology - Chinese Academy of Sciences. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1095D. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 129 records from Total foraminifera counts of multinet PO247/2_MSN1378. 3 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 9 records from Abundance of radiolaria at station UT99-15-2. 6 records from Grünanlagen Stadt Brandenburg an der Havel. 7 records from Nannofossil abundance of Hole 7-64. 32 records from Grundschüler erkunden Schulumgebung. 10768 records from Fungi collection of Jyväskylä University Museum. 2294 records from (Table 10C) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588C. 1100 records from Foraminifera abundance of Hole 64-478. 30 records from Range table from planktonic foraminifers in ODP Hole 170-1042B. 2 records from Abundance of benthos infauna at station PO128/2_276. 66489 records from SLU Aqua Institute of Freshwater Research Swedish Electrofishing Registry - SERS. 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 120 records from Total foraminifera counts of multinet M10/2_MSN319. 48 records from Total foraminifera counts of multinet M21/5_MSN733. 1 records from Microzooplankton abundance and biomass at station TT050_17-5. 439 records from Antarctic and Subantarctic Asteroid zoogeography. 1104 records from (Table 11) Distribution of planktonic foraminifers in ODP Hole 108-657A. 60 records from (Tab. 5) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 13-120, Gorringe Bank southwest of Spain. 79 records from Greater Manchester Ecology Unit - Hare distributions for Greater Manchester. 1234 records from Epiphytic Bryozoa of Posidonia oceanica leaves and scales. 42920 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 245 records from Echuya Survey 2012. 56 records from Planktic foraminifera abundance of Hole 18-182. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 421 records from Range table from benthic foraminifers in ODP Hole 146-892D. 37633 records from Gunma Museum of Natural History, Vascular Plant Specimen. 100 records from Kamptozoa collection of National Museum of Nature and Science. 238 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 542 records from (Table 7) Species composition of clusters, ODP Holes 139-856A and 139-857A. 40460 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 174 records from BIRDRACE Bon(n)apartemöwen. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 19 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_7-CTD84. 4 records from (Table 2) Maastrichtian calcareous nannofossils in DSDP Hole 22-217. 206 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 113-693A. 1048 records from Biodiversidad y dinámica espacio-temporal del ictioplancton de dos sistemas lagunares de la Reserva de la Biósfera de Sian Ka'an. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 42 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 61 records from Planktic foraminifera abundance of Hole 7-64A. 15 records from Planktic foraminifera abundance of Hole 19-191. 36 records from Nannofossil abundance of Hole 37-333. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/011-3. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 110 records from (Table 3) Meiofauna abundance in surface sediments of Cape Lookout. 1617 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 245 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 20362 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 251 records from (Appendix 1) Globigerina bulloides distribution of sediment core M5/2_KL15. 1086 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC17-98. 234 records from Danisco-Wiese. 92 records from Birdrace_TerraCamper-Münster. 9 records from Microplankton abundance at bottle station SEPT-1999-K8. 2072 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 61 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 1177 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 63084 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1996) (AfrOBIS). 1837 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 3630 records from Benthic foraminifera distribution of sediment core GIK17957-2. 2472 records from SMNS Herpetologie. 4599 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 221 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments. 21 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 495 records from Hertfordshire Biological Records Centre - Hertfordshire Lichen Orchard Survey 2011. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 104 records from Planktic foraminifera abundance of Hole 63-473. 25 records from Range table from planktonic foraminifers in ODP Hole 171-1052D. 238 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-967A. 6 records from Description of the females of Anapis castilla and Anapisona bordeaux (Araneae, Anapidae).. 616 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 3. 624 records from Mycology collection, Norwegian Forest and Landscape Institute. 528 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 128-799A. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1020 records from National Museum Of Marine Science & Technology. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 82 records from BIRDRACE Die Ziegeneier. 18 records from Range table from planktonic foraminifers in ODP Hole 182-1128A. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 105 records from Irish Wire Weed (Sargassum muticum) Database. 6913 records from MUST, Insecta. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 19084 records from UAM Bird Collection (Arctos). 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 110 records from Obstwiese Osterberg. 4 records from Trap data WR2, 1648 m. 1440 records from (Figure 6) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642C. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 19 records from DSMZ Collection of Filamentous Fungi and Yeasts. 702 records from (Tab. 15) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 62-463, Western Mid Pacific Mountains. 2353 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 561 records from Herpetile collection, Natural History Museum, University of Oslo. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 49 records from Dörnberg. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 112 records from Werl macht sich auf die Suche. 11 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/009-2. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 22 records from Dellwiger Bach (Dortmund). 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN638. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 5 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC7. 670 records from Bulau. 32 records from Nannofossil abundance in sediment core PS1312-4. 2 records from Föhrenried. 637 records from MNA - Sezione di Genova - (Marine Biological Samples). 114 records from Flora. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 66 records from Calcareous dinoflagellates nominated in grain fraction < 20 µm. 243 records from Cretaceous nannofossils in profile Serre Chaitieu, SE France. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 20 records from (Table 4) Pleistocene to Miocene ostracodes from ODP Hole 104-643A. 156 records from (Table 1) Occurrence of bottom invertebrates in the Canary upwelling area. 47661 records from Programa de repatriación de datos de ejemplares mexicanos. 64 records from Occurrence of mammalia relicts at site Spitalhöhle. 156 records from Total foraminifera counts of multinet M21/1_MSN609. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 213 records from Coccoliths in sediment core PS1113-1. 17 records from Nannofossil abundance of Hole 3-13. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 1892 records from Physical properties and geochemical composition of sediment cores PTA02-04, PTA03-12 and PTA03-13 from Laguna Potrok Aike, Patagonia. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-013. 58 records from Planktic foraminifera counts of sediment core ELT48.011-PC. 120896 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 98 records from Antarctic Amphipoda. 50 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part I. 720 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 126-793A. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE275. 19 records from Pollen profile from Achenhang. 1 rec
Keywords: GBIF; biodiversity; species occurrences